ENGINEERING STUDENTS INTENTION TO USE DUOLINGO FOR MOBILE ASSISTED LANGUAGE LEARNING (MALL) FOR SPANISH AS FOREIGN LANGUAGE: APPLYING THE TECHNOLOGY ACCEPTANCE MODEL - Sushant, Gaurav (International Journal of Psychosocial Rehabilitation, 2020)
Mobile phones are considered an essential tool for language learning, and various research conducted in this regard has reflected the benefits of mobile-assisted language learning (MALL). Nevertheless, few studies on mobile assisted language learning through Duolingo have been conducted on Indian learners. Therefore, this study is an attempt to examine whether the usage of MALL through Duolingo in Spanish as a foreign language among private engineering institute students helped them. To do this research, a survey questionnaire based on the Technology Acceptance Model (TAM) is conducted for collecting data. One hundred fifty students of Vellore Institute of Technology were involved in this survey, and all the respondents were pursuing a Bachelor of Technology (BTech). For this research, a quantitative approach is adopted, and through the survey, we are going to see the perception among the respondents on the utilization of Duolingo for MALL. Moreover, further analysis of the perception of usage will be done based on perceived usefulness (PU) and perceived ease of use (PEoU). The study based on the above two criteria is pertinent because it is an essential aspect of the Technology Acceptance Model (TAM). In the end, the motive of this research is to find out whether the usage of Duolingo for MALL will ameliorate the Spanish teaching and learning process.